Relationship Between Sensation Seeking and Attitude on Reckless Riding Behavior in Jabodetabek, Indonesia - Rahardjo, Imanurul Aisha; Kusumawardhani, Dianti E. (UI Scholars Hub, 2020)
Transportation needs are increasing along with traffic problems, such as traffic accidents, congestion, and density of motorized vehicles. In Indonesia, especially in its large, crowded cities, accidents involving two-wheeled motorized vehicles are frequent. Human factors such as personality and behavior are a cause of accidents involving careless driving. Additionally, sensation seeking and the attitude toward reckless behavior influence the reckless behavior of motorcyclists in Indonesia, especially in the Jabodetabek area. Methods: data were obtained through a self-report questionnaire. The 69 participants (F:40, M:29) were motorbike riders aged 18–35 years who had an Indonesian driving license type C and had ridden a motorcycle daily for a minimum of 2 years. The questionnaire comprised 17 items that measured sensation seeking and attitudes toward reckless riding. Prerequisite for mediating the relationship among the variables, sensation seeking must correlate with attitudes and reckless riding such that the attitude variable that is a mediator must also correlate with reckless riding. Therefore, in this study, the mediating effect of attitudes in the relation between sensation seeking and reckless riding was tested. Our result demonstrates that’s influence of reckless riding attitude as a partial mediator between sensation seeking and reckless riding.